The shining path : love, madness, and revolution in the Andes - Starn, Orin; La Serna, Miguel (W.W. Norton & Company, 2019)
"A narrative history of the unlikely Maoist rebellion that terrorized Peru long after the fall of global communism. The tale of the Shining Path may be the most gripping saga in modern Latin American history, but its full story has never been told. Described by a U.S. State Department cable as 'cold-blooded and bestial, ' this band of Marxist-Leninist-Maoist revolutionaries mounted a guerrilla war in the 1980s that led to more than 60,000 deaths or disappearances. At its helm was the professor-turned-revolutionary Abimael Guzmán, who launched his quixotic insurrection based on outmoded, dogmatic ideology alongside two women: his charismatic young wife, Augusta La Torre, and the formidable Elena Iparaguirre, who abandoned her family to join the war. Orin Starn and Miguel La Serna's narrative also introduces the mountain villagers who organized a fierce resistance, the mercurial black activist María Elena Moyano, and the Nobel Prize-winning novelist Mario Vargas Llosa. Dramatic and engaging, The Shining Path takes the reader into the heart of this brutal rebellion, and the lives and country it nearly destroyed"--